The Relationship Between Fat Tissue & Lean Body Mass and Sit to Stand Task in Obese Individuals - AVCI, ENDER ERSİN; TİMURTAŞ, EREN; AKGÜN, İREM; DEMİRBÜKEN, İLKŞAN; POLAT, MİNE GÜLDEN (MARMARA UNIV, INST HEALTH SCIENCES, 2021)
Objective: Obesity, currently one of the important health issues, can be defined through Fat Tissue Mass (FTM) and Lean Body Mass (LBM). The study aimed to investigate to what extent do FTM and LBM are associated with movement strategies of Sit-to-Stand (STS) task in individuals with obesity. Methods: Forty-nine obese individuals (52,83 +/- 7,39) with no diagnosis of any health condition included in the study. The Balance Master System was used to evaluate the STS movement. STS task was analyzed by means of Weight Transfer Time (WTT) (second), Rising Index (RI) (force exerted by legs-%Body Weight), the Center of Gravity (COG) sway velocity (degrees per second). The FTM and LBM were regressed against each STS parameter including age as a covariate. Results: The regression models could explain 10-21% of the variabilities in STS parameters: RI (21%), COG sway velocity (11%), WTT (10%). FTM significantly related to RI (beta: -0.287, p=0.040), but not with COG sway velocity (beta: 0.270, p=0.073) and WTT (beta: - 0.038, p=0.802). LBM was significantly associated with RI (beta: 0.435, p=0.003); yet, not with COG sway velocity (beta: -0.100, p=0.066), WTT (beta: -0.092, p=0.549). Conclusion: This study revealed that FTM and LBM can explain the significant percent of the variation in RI during STS task, meaning a decrease in FTM and an increase in LBM provided support to rise during STS task. Moreover, an increase in FTM deteriorated postural stability. Improving LBM and decreasing FTM would be an effective strategy to improve STS in the obese population to increase their agility and could encourage physical activity participation.
Keywords: Obesity; Fat Tissue Mass; Lean Body Mass; Sit to Stand Task; MOVEMENT; STRENGTH